Problem of automation of situational management of protection of zones of the responsibility - Alekseev, V.A.; Mostovoy, V.V.; Tereshchenko, V.S.; Yalovets, A.L. (PROBLEMS IN PROGRAMMING, 2025)
The opportunity of automation of process of the analysis of operative conditions in a zone of the responsibility of security structures and estimations of a developed situation is considered. Functional tasks of systems of situational management are analyzed, possible situations with objects of the control are defined and examples of their estimation are resulted. The choice of expedient mathematical methods and models of an artificial intellect for automation of the decision of a task of an estimation of situations is carried out and the task of development of corresponding software is formulated. Prombles in programming 2011; 4: 96-107